Education and Concern of Zakat Agencies - Munadi, Muhammad; Umar, Ahmad; Anggraini, Novianni (LP2M IAIN kUDUS, 2021)
This research examined the zakat agencies which concern to the education program. This research used library reserach. The documents used were the ins and outs of zakat agencies that have educational development programs. These documents were taken from the website of zakat agencies both BAZNAS and Dompet Dhuafa (DD). The data taken consisted of information, data, and news related to the alocation of zakat for education, education variations of education program, the type of zakat disbursement, and the path alocation in education. The data analysis was descriptive qualitative analysis. The results showed that BAZNAS gave scholarships from Elementary School – Undergraduate (Islamic Religious Higher Education and Public Higher Education) and in-country scholarships. DD gave scholarships for undergraduate – Post graduate (Islamic Religious Higher Education and Public Higher Education), in-country scholarships, overseas scholarships, middle and high school level, education for teacher and literacy school. Zakat agencies are very varied in the development of education especially in Dompet Dhuafa from upstream to downstream.